Austenitic antibacterial stainless steel material and processing technology thereof

Corrosion of austenitic stainless steel materials in corrosive liquids and microorganisms is solved by combining epoxy resin with eugenol-based diol and isocyanate-based end-capped polymers to form a modified coating and coat it on the surface of austenitic stainless steel. Problem, improving antibacterial and wear resistance, enhancing the adhesion and mechanical strength of the coating.

CN118852954BActive Publication Date: 2025-01-07JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411337681.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Austenitic stainless steel materials are prone to corrosion when exposed to corrosive liquids, and microorganisms are also one of the causes of corrosion damage, and lack effective antibacterial properties.

Method used

By reacting the epoxy resin with methacrylic acid and bonding with eugenol-based diol and isocyanate-based end-capped polymer, a modified epoxy resin coating is formed, and crosslinking is initiated by ultraviolet initiator, coated on austenite The surface of stainless steel forms antibacterial stainless steel material.

Benefits of technology

It improves the antibacterial properties, wear resistance and mechanical strength of the coating, enhances the adhesion properties and the overall performance of the coating, and effectively protects austenitic stainless steel materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of stainless steel materials, specifically to a kind of austenitic antibacterial stainless steel material and its processing technology. The present invention first modifies epoxy resin with methacrylic acid, reacts with carboxyl and epoxy groups to obtain methacrylic acid grafted epoxy resin; eugenol with antibacterial performance is reacted with DL-1,4-dichloro-2,3-butanediol in a molar ratio of 2:1 to obtain eugenol-based diol, and then eugenol-based diol is mixed with ethylene glycol to obtain a mixed diol, and reacted with isophorone diisocyanate to obtain an isocyanate-terminated polymer; by reacting the isocyanate group with the hydroxyl group in the epoxy resin, the isocyanate-terminated polymer containing the eugenol group is introduced into the side chain of the methacrylic acid grafted epoxy resin to obtain a modified epoxy resin. The modified epoxy resin is applied to the surface of the austenitic stainless steel material, and a coating with an antibacterial effect is formed by ultraviolet irradiation to prevent the material from being corroded by bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel materials, in particular to an austenitic antibacterial stainless steel material and a processing technology thereof. Background Art

[0002] Austenitic stainless steel refers to stainless steel materials with austenite structure at room temperature. Due to its excellent corrosion resistance, wear resistance, toughness, processability, mechanical properties, chemical stability and non-toxicity, it is widely used in aviation, ocean, medical engineering, petrochemical and other fields. During the use of austenitic stainless steel materials, they are often exposed to corrosive liquids such as acids, alkalis, salts, etc., which cause corrosion. By coating the surface of stainless steel materials with resin coatings to form a protective layer, not only can the chemical corrosion resistance be effectively improved, but also the problem of the surface of stainless steel materials being contaminated by water, grease, etc. can be avoided. In addition, microorganisms are also one of the reasons for the corrosion and damage of stainless steel materials. Therefore, it is very necessary to invent an austenitic antibacterial stainless steel material. Summary of the invention

[0003] The object of the present invention is to provide an austenitic antibacterial stainless steel material and a processing technology thereof to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0005] Step 1: Disperse epoxy resin E51 in toluene, heat to 80-90°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine, continue to slowly heat to 100-110°C, keep the temperature for 2-3 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store in dark;

[0006] Step 2: Disperse eugenol in an ethanol mixed solution, stir evenly, heat to 70-80°C, then dropwise add DL-1,4-dichloro-2,3-butanediol, and react for 12-15 hours after the dropwise addition is complete; then cool naturally and stand for 16-20 hours. After the reaction is completed, filter, wash, recrystallize from anhydrous ethanol, filter twice, and vacuum dry at 50-60°C to obtain eugenol-based diol;

[0007] Step 3: Mix eugenol-based diol and ethylene glycol to obtain a mixed diol; dehydrate the raw materials, add isophorone diisocyanate to the mixed diol at 45-50° C. and nitrogen environment, stir evenly, drop n-butyltin dilaurate, and increase the reaction temperature to 65-75° C., react for 3-4 hours, and obtain an isocyanate-terminated polymer;

[0008] Step 4: After mixing the methacrylic acid grafted epoxy resin and the isocyanate-terminated polymer, add anhydrous acetone, raise the temperature to 40-50°C, and stir the reaction for 6-8 hours to obtain a modified epoxy resin; mix the modified epoxy resin and the photoinitiator, stir evenly, and apply it on the surface of the austenitic stainless steel material. After irradiating with ultraviolet light for 10-15 minutes, place it in an environment of 25-30°C for 2-3 hours to obtain an austenitic antibacterial stainless steel material.

[0009] Furthermore, in step 1, epoxy resin E51 and methacrylic acid are reacted at a molar ratio of epoxy group to carboxyl group of 1:1.

[0010] Furthermore, in step 2, the ethanol mixed solution includes components in amounts, by weight, of 13 to 14 parts of anhydrous potassium carbonate, 0.6 to 0.9 parts of potassium iodide, and 100 parts of anhydrous ethanol.

[0011] Further, in step 2, eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1.

[0012] Furthermore, in step 3, eugenol-based glycol and ethylene glycol are mixed in a weight ratio of 1:(4-5) to obtain a mixed diol.

[0013] Furthermore, in step 3, the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:(1.3-1.5).

[0014] Furthermore, in step 4, 88-93% of the methacrylic acid grafted epoxy resin and 7-12% of the isocyanate-terminated polymer are mixed by weight percentage.

[0015] Furthermore, in step 4, the solid content of the modified epoxy resin is 40-45%.

[0016] Furthermore, in step 4, the thickness of the surface coating of the austenitic stainless steel is 0.3-0.5 mm.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention first reacts methacrylic acid with an epoxy resin, introduces an unsaturated carbon-carbon double bond into the epoxy resin, and obtains a methacrylic acid grafted epoxy resin; uses eugenol with antibacterial properties as a raw material, reacts it with DL-1,4-dichloro-2,3-butanediol at a molar ratio of 2:1 to obtain eugenol-based diol, then mixes the eugenol-based diol with ethylene glycol, and reacts with isophorone diisocyanate at a molar ratio of hydroxyl to isocyanate of 1:(1.3-1.5) to obtain an isocyanate-terminated polymer; mixes the isocyanate-terminated polymer with the epoxy resin, and introduces the isocyanate-terminated polymer containing the eugenol group into the side chain of the methacrylic acid grafted epoxy resin through the reaction of the isocyanate group with the hydroxyl group in the epoxy resin, which, on the one hand, gives the coating good antibacterial properties, and on the other hand, the eugenol group contains a rigid benzene ring structure, so that the wear resistance of the coating is also improved. Since both ends of the isocyanate-terminated polymer contain isocyanate groups, the degree of cross-linking between the epoxy resin molecular segments is improved to a certain extent; in addition, the eugenol group in the modified epoxy resin side chain contains unsaturated carbon-carbon double bonds, which can be further polymerized and cross-linked with the carbon-carbon double bonds in the epoxy resin main chain under the action of photoinitiators. Therefore, the cross-linking degree of the epoxy resin is significantly improved, and the adhesion, wear resistance and mechanical strength of the coating are enhanced.

[0018] In addition, it should be noted that the amount of isocyanate-terminated polymer used to modify the epoxy resin is not the more the better. Excessive use of the isocyanate-terminated polymer will lead to an excessively high degree of crosslinking of the modified epoxy resin, resulting in an increase in the viscosity of the coating. On the other hand, the compatibility between the isocyanate-terminated polymer and the epoxy resin will decrease, both of which will lead to a decrease in the performance of the coating. Therefore, by weight percentage, 88-93% of methacrylic acid grafted epoxy resin is mixed with 7-12% of isocyanate-terminated polymer to obtain a modified epoxy resin coating with better performance, which can improve the antibacterial properties of austenitic stainless steel materials and play a good protective role. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Materials and sources used in the present invention: Epoxy resin E51 comes from Guangzhou Chaoying Chemical Co., Ltd., item number 003; Photoinitiator is photoinitiator 1173, which comes from Shanghai Houcheng Fine Chemical Co., Ltd.

[0021] Embodiment 1: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0022] Step 1: Disperse epoxy resin E51 in toluene, heat to 80°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 100°C, keep the temperature for reaction for 2 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0023] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide, and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, and then heated to 70° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 12 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 16 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol, and filtered twice, and vacuum dried at 50° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0024] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 45° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 65° C. and reacted for 3 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0025] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 40°C, and stirred for reaction for 6 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount used is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 10 minutes, it is placed at 25°C for 2 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0026] Embodiment 2: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0027] Step 1: Disperse epoxy resin E51 in toluene, heat to 85°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 105°C, keep the temperature for reaction for 2.5 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0028] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, heated to 75° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 14 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 18 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol and filtered twice, and vacuum dried at 55° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0029] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 70° C. and reacted for 3.5 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0030] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 45°C, stirred and reacted for 7 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount used is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly and coated on the surface of austenitic stainless steel material, after ultraviolet light irradiation for 15 minutes, placed at 30°C for 2.5 hours, a coating with a thickness of 0.3 mm is formed on the surface of the austenitic stainless steel, and an austenitic antibacterial stainless steel material is obtained.

[0031] Embodiment 3: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0032] Step 1: Disperse epoxy resin E51 in toluene, heat to 90°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 110°C, keep the temperature for reaction for 3 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0033] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide, and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, and then heated to 80° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 15 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 20 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol, and filtered twice, and vacuum dried at 60° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0034] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 75° C. and reacted for 4 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0035] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 50°C, stirred and reacted for 8 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount used is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly and coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 15 minutes, it is placed at 30°C for 3 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0036] Embodiment 4: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0037] Step 1: Disperse epoxy resin E51 in toluene, heat to 80°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 105°C, keep the temperature for reaction for 2.5 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0038] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide, and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, and then heated to 70° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 12 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 20 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol, and filtered twice, and vacuum dried at 55° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0039] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:4.8 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 45° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 75° C. and reacted for 3 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0040] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 40°C, and stirred for reaction for 6.5 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 12 minutes, it is placed at 30°C for 2.5 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0041] Embodiment 5: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0042] Step 1: Disperse epoxy resin E51 in toluene, heat to 85°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 100°C, keep the temperature for reaction for 3 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0043] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, heated to 75° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 13 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 17 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol and filtered twice, and vacuum dried at 55° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0044] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:4.5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 75° C. and reacted for 3 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0045] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 45°C, and stirred for reaction for 7.5 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 15 minutes, it is placed at 30°C for 2 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0046] Embodiment 6: An austenitic antibacterial stainless steel material and a processing technology thereof, comprising the following steps:

[0047] Step 1: Disperse epoxy resin E51 in toluene, heat to 90°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 105°C, keep the temperature for reaction for 2.5 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0048] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide, and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, and then heated to 75° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 15 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 19 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol, and filtered twice, and vacuum dried at 60° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0049] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:4 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 70° C. and reacted for 3.5 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0050] Step 4: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 45°C, and stirred for reaction for 6.5 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount used is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 13 minutes, it is placed at 25°C for 3 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0051] Comparative Example 1: No eugenol diol was added, and other parameters were the same as those in Example 1.

[0052] Step 1: Disperse epoxy resin E51 in toluene, heat to 80°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 100°C, keep the temperature for reaction for 2 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0053] Step 2: Dehydrate the raw materials, add isophorone diisocyanate to ethylene glycol at 45°C under nitrogen environment, stir evenly, then drop n-butyltin dilaurate (in an amount of 0.5% of the total weight of the reactants), and raise the reaction temperature to 65°C, react for 3 hours, and obtain an isocyanate-terminated polymer; wherein ethylene glycol and isophorone diisocyanate react at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0054] Step 3: By weight percentage, 90% methacrylic acid grafted epoxy resin and 10% isocyanate-terminated polymer are mixed, dispersed in anhydrous acetone, heated to 40°C, and stirred for reaction for 6 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and a photoinitiator (the amount is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 10 minutes, it is placed at 25°C for 2 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0055] Comparative Example 2: Methacrylic acid is not grafted onto the epoxy resin, and other parameters are the same as those in Example 2.

[0056] Step 1: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, heated to 75° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 14 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 18 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol and filtered twice, and vacuum dried at 55° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0057] Step 2: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 70° C. and reacted for 3.5 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0058] Step 3: By weight percentage, 90% epoxy resin and 10% isocyanate-terminated polymer are mixed and dispersed in anhydrous acetone, the temperature is raised to 45°C, and the reaction is stirred for 7 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and the photoinitiator (the amount is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 15 minutes, it is placed at 30°C for 2.5 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0059] Comparative Example 3: The amount of the isocyanate-terminated polymer was increased, and the other parameters were the same as those in Example 3.

[0060] Step 1: Disperse epoxy resin E51 in toluene, heat to 90°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine (the amount is 0.5% of the total weight of the reactants), continue to slowly heat to 110°C, keep the temperature for reaction for 3 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store it in the dark; wherein the epoxy resin E51 and methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;

[0061] Step 2: 13.8 g of anhydrous potassium carbonate, 0.69 g of potassium iodide, and 100 g of anhydrous ethanol are mixed to obtain an ethanol mixed solution; eugenol is dispersed in the ethanol mixed solution, stirred evenly, and then heated to 80° C., and then DL-1,4-dichloro-2,3-butanediol is added dropwise, and the mixture is reacted for 15 hours after the addition is completed; the mixture is then naturally cooled and allowed to stand for 20 hours. After the reaction is completed, the crude product obtained by the reaction is filtered, washed, recrystallized from anhydrous ethanol, and filtered twice, and vacuum dried at 60° C. to obtain eugenol-based diol; wherein eugenol and DL-1,4-dichloro-2,3-butanediol are reacted in a molar ratio of 2:1;

[0062] Step 3: eugenol-based diol and ethylene glycol are mixed at a weight ratio of 1:5 to obtain a mixed diol; the raw materials are dehydrated, and isophorone diisocyanate is added to the mixed diol at 50° C. under a nitrogen environment, and after stirring evenly, n-butyltin dilaurate (the amount is 0.5% of the total weight of the reactants) is dropped, and the reaction temperature is increased to 75° C. and reacted for 4 hours to obtain an isocyanate-terminated polymer; wherein the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:1.5;

[0063] Step 4: By weight percentage, 80% methacrylic acid grafted epoxy resin and 20% isocyanate-terminated polymer are mixed and dispersed in anhydrous acetone, the temperature is raised to 50°C, and the reaction is stirred for 8 hours to obtain a modified epoxy resin with a solid content of 40%; the modified epoxy resin and the photoinitiator (the amount is 0.5% of the total weight of the modified epoxy resin) are mixed, stirred evenly, and then coated on the surface of the austenitic stainless steel material. After ultraviolet light irradiation for 15 minutes, it is placed at 30°C for 3 hours to form a coating with a thickness of 0.3 mm on the surface of the austenitic stainless steel to obtain an austenitic antibacterial stainless steel material.

[0064] Experiment: Examples 1 to 6 and Comparative Examples 1 to 3 were tested, and the test results are shown in the following table.

[0065] Adhesion test: Refer to GB∕T 1720-2020 to test the adhesion of the coating on the surface of austenitic stainless steel;

[0066] Hardness test: Refer to GB / T 6739-2022 to test the hardness of the coating;

[0067] Impact resistance test: Refer to GB / T 1732-2020 to test the impact resistance of the coating;

[0068] Antibacterial performance test: Gram-negative Escherichia coli (E. coli) was cultured in LB nutrient broth at 37°C for 12 hours to a bacterial concentration of 1×10 8 CFU / mL, dilute the bacterial solution to a certain concentration, take 2mL of the bacterial solution and continue to culture for 3h; mix the epoxy resin and photoinitiator prepared in Examples 1-6 and Comparative Examples 1-3 and apply them on the culture medium, place them under 30℃ environment for 3h after ultraviolet irradiation for 15min, and form a coating with a thickness of 0.3mm; take 30μL of the cultured bacterial solution, evenly apply it on the culture dish, and count the number of colonies on the culture dish after culturing at 37℃ for 24h, and take the culture dish bacterial solution without coating as the blank group. Antibacterial rate (A) calculation formula: A=(Nc-Ns) / Nc×100%; where Nc is the number of colonies in the blank control group, and Ns is the number of colonies in the sample group.

[0069]

[0070] Conclusion: The experimental results of Examples 1 to 6 show that the austenitic antibacterial stainless steel prepared by the present invention has excellent performance. The experimental results of Example 1 and Comparative Example 1 show that eugenol-based diol can improve the adhesion effect and hardness of the epoxy resin coating, while also imparting good antibacterial properties; the experimental results of Example 2 and Comparative Example 2 show that after the epoxy resin is grafted with methacrylic acid, the adhesion performance of the coating is improved; the data of Example 3 and Comparative Example 3 show that excessive use of isocyanate-terminated polymers will reduce the performance of the coating.

[0071] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for austenitic antibacterial stainless steel material, characterized by: The following steps are involved: Step 1: Disperse epoxy resin E51 in toluene, heat to 80-90°C, add methacrylic acid and catalyst N,N-dimethylbenzylamine, continue to slowly heat to 100-110°C, keep the temperature for 2-3 hours, cool and remove the solvent to obtain methacrylic acid grafted epoxy resin, and store in dark; Step 2: Disperse eugenol in an ethanol mixed solution, stir evenly, heat to 70-80°C, then dropwise add DL-1,4-dichloro-2,3-butanediol, and react for 12-15 hours after the dropwise addition is complete; then cool naturally and stand for 16-20 hours. After the reaction is completed, filter, wash, recrystallize from anhydrous ethanol, filter twice, and vacuum dry at 50-60°C to obtain eugenol-based diol; Step 3: Mix eugenol-based diol and ethylene glycol to obtain a mixed diol; dehydrate the raw materials, add isophorone diisocyanate to the mixed diol at 45-50° C. and nitrogen environment, stir evenly, drop n-butyltin dilaurate, and increase the reaction temperature to 65-75° C., react for 3-4 hours, and obtain an isocyanate-terminated polymer; Step 4: by weight percentage, 88-93% of methacrylic acid grafted epoxy resin and 7-12% of isocyanate-terminated polymer are mixed, anhydrous acetone is added, the temperature is raised to 40-50° C., and the reaction is stirred for 6-8 hours to obtain a modified epoxy resin; The modified epoxy resin and the photoinitiator are mixed, stirred evenly and then coated on the surface of the austenitic stainless steel material. After irradiation with ultraviolet light for 10 to 15 minutes, the material is placed in an environment of 25 to 30° C. for 2 to 3 hours to obtain an austenitic antibacterial stainless steel material.

2. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized in that: In step 1, epoxy resin E51 and methacrylic acid are reacted in a molar ratio of epoxy group to carboxyl group of 1:

1.

3. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized in that: In step 2, the ethanol mixed solution includes components in amounts, by weight, of 13 to 14 parts of anhydrous potassium carbonate, 0.6 to 0.9 parts of potassium iodide, and 100 parts of anhydrous ethanol.

4. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized in that: In step 2, eugenol and DL-1,4-dichloro-2,3-butanediol are reacted at a molar ratio of 2:

1.

5. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized in that: In step 3, eugenol-based diol and ethylene glycol are mixed in a weight ratio of 1:(4-5) to obtain a mixed diol.

6. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized by: In step 3, the mixed diol and isophorone diisocyanate are reacted at a molar ratio of hydroxyl group to isocyanate group of 1:(1.3-1.5).

7. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized by: In step 4, the solid content of the modified epoxy resin is 40-45%.

8. The processing technology of austenitic antibacterial stainless steel material according to claim 1 is characterized by: In step 4, the thickness of the coating on the surface of the austenitic stainless steel is 0.3-0.5 mm.

9. Austenitic antibacterial stainless steel material obtained by the processing technology according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Eugenol side group-containing polyurethane coating as well as preparation method and application thereof

    CN118027797A

  • Preparation process of environment-friendly decorative plate capable of releasing negative oxygen ions

    CN118165338A